(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
This article deals with the key factors and pedagogical opportunities involved in fostering a safe information environment among youth. Through analytical research methods, the paper identifies the challenges young people face in the digital space, including misinformation, cyberbullying, and digital addiction. It also examines the role of educational institutions, teachers, and digital literacy programs in promoting safe and responsible online behavior. The findings offer practical recommendations for integrating information safety into educational practices and curricula to build a more secure digital environment for young users.